1966
DOI: 10.1002/ar.1091540311
|View full text |Cite
|
Sign up to set email alerts
|

Pathological changes in adipose tissue of obese mice

Abstract: Gonadal and perirenal fat pads from markedly obese mice show pathological changes associated with the appearance of many large macrophages, small mononuclear cells resembling lymphocytes, and polymorphonuclear cells. The first recognizable changes are always associated with necrosis of the fat cell membrane. Advanced stages also show reduction of the number of fat cells, formation of large fat vacuoles and cysts, and predominance of innumerable pathological cells. The extent of tissue changes varies considerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

1970
1970
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 10 publications
2
14
1
Order By: Relevance
“…It is interesting that we found more aP2 Ϫ macrophages in omental fat than subcutaneous fat in these severely obese patients. A greater number of macrophages in adipose tissue of murine models of obesity have been reported (21,45). This process was more apparent in intra-abdominal depots than in the subcutaneous depot in mice (21).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It is interesting that we found more aP2 Ϫ macrophages in omental fat than subcutaneous fat in these severely obese patients. A greater number of macrophages in adipose tissue of murine models of obesity have been reported (21,45). This process was more apparent in intra-abdominal depots than in the subcutaneous depot in mice (21).…”
Section: Discussionmentioning
confidence: 90%
“…A greater number of macrophages in adipose tissue of murine models of obesity have been reported (21,45). This process was more apparent in intra-abdominal depots than in the subcutaneous depot in mice (21). The presence of macrophages correlates with increasing weight and fat cell size and occurred primarily by recruitment of monocytes from the circulation in mice (44).…”
Section: Discussionmentioning
confidence: 91%
“…These observations later inspired studies connecting the anti-diabetic effects of high dose salsalate with inflammatory signaling (discussed below). In addition, careful pathologists examining tissues of animal models of obesity in the 1960s had reported the infiltration of immune cells, such as macrophages and mast cells, into the adipose tissue (Hausberger, 1966; Hellman, 1965), but this mostly escaped the attention of scientists, including myself, until much later. Hence, despite all of these early observations and lines of evidence, the potential for an immunological nature of metabolic disease and its relation to obesity was largely disregarded for decades, and the cellular and molecular mechanisms that lead to abnormal insulin action, production, and glucose metabolism in obesity remained elusive.…”
Section: Impact Of Immunity On Metabolismmentioning
confidence: 99%
“…Although evidence for crosstalk between immunity and metabolism has sporadically existed in the literature for quite some time (Ardawi and Newsholme, 1983; Hausberger, 1966; Williamson, 1901), the contemporary fields of cellular and tissue immunometabolism can trace their origins to a handful of pivotal papers. For cellular immunometabolism, the classic paper by Thompson and colleagues in 2002 demonstrated that the costimulation of T cells with anti-CD28 increased glucose uptake and glycolysis to support anaplerotic metabolism of proliferating lymphocytes (Frauwirth et al, 2002).…”
mentioning
confidence: 99%